COMPARATIVE FASTNESS ASSESSMENT PERFORMANCE OF CELLULOSIC FIBERS DYED USING NATURAL COLORANTS (Biological Sciences - PJSIR, 2001)
Two natu ral dyes of plant origin , namely bixi n and curcu min were extracted , purified and used as color additi ves i n two i               fibrous constructions of floor carpet and cotton fabric by the 'exhaust dyeing' technique. The fastness properties of these dyes both to l ight and washi ng and thei r use were assessed comparatively. Curcumi n showed higher average  fastnessrati ngs to l ight and to alkaline wash over its bixin  counterpart.